Hybrid Projection Algorithm for Two Countable Families of Hemirelatively Nonexpansive Mappings and Applications. (7th October 2013) - Wang, Zi-Ming; Kumam, Poom
Abstract : Two countable families of hemirelatively nonexpansive mappings are considered based on a hybrid projection algorithm. Strong convergence theorems of iterative sequences are obtained in an uniformly convex and uniformly smooth Banach space. As applications, convex feasibility problems, equilibrium problems, variational inequality problems, and zeros of maximal monotone operators are studied.